The Transpolar Drift as a Source of Riverine and Shelf‐Derived Trace Elements to the Central Arctic Ocean. Issue 5 (6th May 2020) - Charette, Matthew A.; Kipp, Lauren E.; Jensen, Laramie T.; Dabrowski, Jessica S.; Whitmore, Laura M.; Fitzsimmons, Jessica N.; Williford, Tatiana; Ulfsbo, Adam; Jones, Elizabeth; Bundy, Randelle M.; Vivancos, Sebastian M.; Pahnke, Katharina; et al.
Abstract: A major surface circulation feature of the Arctic Ocean is the Transpolar Drift (TPD), a current that transports river‐influenced shelf water from the Laptev and East Siberian Seas toward the center of the basin and Fram Strait. In 2015, the international GEOTRACES program included a high‐resolution pan‐Arctic survey of carbon, nutrients, and a suite of trace elements and isotopes (TEIs). The cruises bisected the TPD at two locations in the central basin, which were defined by maxima in meteoric water and dissolved organic carbon concentrations that spanned 600 km horizontally and 25–50 m vertically. Dissolved TEIs such as Fe, Co, Ni, Cu, Hg, Nd, and Th, which are generally particle‐reactive but can be complexed by organic matter, were observed at concentrations much higher than expected for the open ocean setting. Other trace element concentrations such as Al, V, Ga, and Pb were lower than expected due to scavenging over the productive East Siberian and Laptev shelf seas. Using a combination of radionuclide tracers and ice drift modeling, the transport rate for the core of the TPD was estimated at 0.9 ± 0.4 Sv (10 6 m 3 s −1 ). This rate was used to derive the mass flux for TEIs that were enriched in the TPD, revealing the importance of lateral transport in supplying materials beneath the ice to the central Arctic Ocean and potentially to the North Atlantic Ocean via Fram Strait. Continued intensification of the Arctic hydrologic cycle and permafrost degradation will likely lead to an increase in the flux of TEIs into the Arctic Ocean. Plain Language Summary: A major feature of the Arctic Ocean circulation is the Transpolar Drift (TPD), a surface current that carries ice and continental shelf‐derived materials from Siberia across the North Pole to the North Atlantic Ocean. In 2015, an international team of oceanographers conducted a survey of trace elements in the Arctic Ocean, traversing the TPD. Near the North Pole, they observed much higher concentrations of trace elements in surface waters than in regions on either side of the current. These trace elements originated from land, and their journey across the Arctic Ocean is made possible by chemical reactions with dissolved organic matter that originates mainly in Arctic rivers. This study reveals the importance of rivers and shelf processes combined with strong ocean currents in supplying trace elements to the central Arctic Ocean and onward to the Atlantic. These trace element inputs are expected to increase as a result of permafrost thawing and increased river runoff in the Arctic, which is warming at a rate much faster than anywhere else on Earth. Since many of the trace elements are essential building blocks for ocean life, these processes could lead to significant changes in the marine ecosystems and fisheries of the Arctic Ocean. Key Points: The Transpolar Drift is a source of shelf‐ and river‐derived elements to the central Arctic Ocean The TPD is rich in dissolved organic matter (DOM), which facilitates long‐range transport of trace metals that form complexes with DOM Margin trace element fluxes may increase with future Arctic warming due to DOM release from permafrost thaw and increasing river discharge